2014
DOI: 10.1016/j.jcjd.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Use of an Online Patient Portal on Diabetes Outcomes

Abstract: Accessing an online patient portal is associated with improved glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 24 publications
2
84
0
Order By: Relevance
“…Lau et al 26 examined the impact of online patient portal usage on glycemic control among patients newly referred to a diabetologist. Factors potentially adversely affecting portal use included level of health literacy, diabetes knowledge, and familiarity with internet technologies.…”
mentioning
confidence: 99%
“…Lau et al 26 examined the impact of online patient portal usage on glycemic control among patients newly referred to a diabetologist. Factors potentially adversely affecting portal use included level of health literacy, diabetes knowledge, and familiarity with internet technologies.…”
mentioning
confidence: 99%
“…8 Lau et al used propensity score matching in a sample of 157 patients with type 2 diabetes and determined that EM users were more likely to achieve an HbA1c of 7% or less at 6 months compared with nonusers. 6 However, message content and type of diabetes were not reported in any of these studies.…”
Section: Discussionmentioning
confidence: 90%
“…4 Some studies reported that EM is associated with lower HbA1c levels. 2,[5][6][7][8] Thus far, studies regarding EM have not differentiated between type 1 and type 2 diabetes, examined message content, or examined the impact of EM on hospital or emergency department (ED) visits. This retrospective cohort study examines the relationship between EM and HbA1c levels, emergency room visits, and hospital admissions.…”
mentioning
confidence: 99%
“…No significant differences were observed at 12 months (−1.14% vs. −0.95%, P=0.133). In a retrospective cohort study, Lau et al (27) found that, compared to patient web portal nonusers, a higher proportion of users achieved HbA1c <7% at follow-up (56% vs. 32%, P<0.031). Tutino et al (28) conducted a randomized controlled trial comparing web portals for diabetic patients alone vs. patient web portal plus nurse-coordinated follow-up visits.…”
Section: Resultsmentioning
confidence: 99%